A model for the identification of challenges to blended learning - E. A. Draffan; Peter Rainger (Association for Learning Technology, 2006)
A model for an inclusive approach to the identification of challenges to blended learning as a means to identify educational accessibility issues is presented. By focusing on both the learner and teacher perspectives, the model encompasses a broad range of factors, including learner characteristics, learning and teaching environments, interactions and activities. The proposed model provides a starting point for the identification of challenges to learning from a socio-cultural perspective rather than a medical or rehabilitation perspective. This holistic perspective is key to moving ‘thinking' towards a more inclusive learning approach that embraces the needs of all learners, regardless of a defined disability.